Improper integrals, an excursion to classical calculus - Zeitler, Herbert (Teaching Mathematics and Computer Science, 2010)
The aim of this paper is to show in what way we investigated improper integrals in the classroom. It was very important to calculate explicitly a lot of examples. Doing so, a criterion was developed. With step curves and infinite series we had a quick look at the mathematical background. The shot in the universe showed that improper integrals are needed in physics.